Mosadi ke Motho: Masenya’s contribution to indigenous gender theorisation - Nqambaza, Palesa (Old Testament essays, 2025)
This article engages Madipoane Masenya’s Bosadi approach as a critical framework for re-imagining gender from an indigenous African perspective. Rooted in African womanist theology, Bosadi offers an epistemological alternative to Western gender constructs, foregrounding the lived experiences and intellectual agency of African womxn. Drawing on socio-linguistic analysis, the article interrogates the lexical and philosophical significance of the term mosadi, revealing its divergence from the Western category of "woman." Through a close reading of linguistic forms such as mosadi and umfazi, the study uncovers embedded cultural values grounded in ubuntu/botho, where personhood is communal and ethically anchored. The Bosadi approach is positioned as a transformative tool for scholars grappling with the entanglements of race, gender and colonial history in South Africa. Ultimately, this article affirms the importance of centring indigenous knowledge systems in feminist scholarship and demonstrates the expansive intellectual possibilities that Bosadi brings to decolonial gender discourse.